Information and Communications Security: 16th International Conference, ICICS 2014, Hong Kong, China, December 16-17, 2014, Revised Selected Papers - International Conference on Information and Communications Security; Hui, Lucas Chi-Kwong (LNCS sublibrary. SL 4, Security and cryptology, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 16th International Conference on Information and Communications Security, ICISC 2014, held in Hong Kong, China, in December 2014. The 22 revised full papers including two invited talks presented were carefully selected from 90 submissions. The papers provide the latest results in research, development and applications in the field of information security and cryptology.